Inovasi Pelayanan Publik di Dinas Pelayanan Terpadu Satu Pintu di Daerah Otonom Kota Depok Provinsi Jawa Barat - Rusmiyati Rusmiyati (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This study aims to describe and analyze and interpret 1) the role of DPMPTSP in realizing innovative licensing and non-licensing services in Depok City; 2) The role of planning, leadership, human resources apparatus, and organizational culture; and 3) DPMPTSP's strategy for licensing and non- licensing service innovation in Depok City, West Java Province. As for the theory used to uncover the problems in this study, the theory of public service innovation developed by Rachel Asworth and friends as stated in the framework of thought. Through a qualitative method with a descriptive approach with a spiral analysis model by John W. Creswell, it was found that 1) the organizational environment, both internal and external DPMPTSP plays a role in the innovation of public services in Depok City; 2) The role of planning, leadership, apparatus human resources, and organizational culture that is built on DPMPTSP is a force to realize Public Service Innovation in Depok City; and 3) Strategy through an internal and external collaboration of local government and organizational learning is the trigger for realizing public service innovation in Depok City, West Java Province.